2012
DOI: 10.1055/s-0032-1310011
|View full text |Cite
|
Sign up to set email alerts
|

Fully covered self-expandable metallic stents in benign biliary strictures: a multicenter study on efficacy and safety

Abstract: Despite the noteworthy migration rate, FCSEMSs should be considered effective for refractory benign biliary strictures. Further studies are needed to assess their role as a first approach in the management of BBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 11 publications
(19 reference statements)
2
79
3
Order By: Relevance
“…We found two retrospective comparative studies comparing plastic and metallic stents (6,15) . Tarantino et al (15) compared the outcomes of patients with failure of the multiple plastic stenting strategy sent to metallic stenting (salvage therapy group) with patients sent directly to metallic stenting as a first line treatment (first line treatment group).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We found two retrospective comparative studies comparing plastic and metallic stents (6,15) . Tarantino et al (15) compared the outcomes of patients with failure of the multiple plastic stenting strategy sent to metallic stenting (salvage therapy group) with patients sent directly to metallic stenting as a first line treatment (first line treatment group).…”
Section: Discussionmentioning
confidence: 99%
“…Tarantino et al (15) compared the outcomes of patients with failure of the multiple plastic stenting strategy sent to metallic stenting (salvage therapy group) with patients sent directly to metallic stenting as a first line treatment (first line treatment group). The authors showed that the sustained clinical success rate was higher in the salvage therapy group when compared to the first line therapy group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with plastic stents, cSEMS showed a high rate of stricture resolution and fewer endoscopic procedures. Therefore, cSEMS was widely used and accepted for the treatment of benign biliary stricture (7,10). However, the endoscopic placement of stents to relieve biliary stricture should take into account the causes of biliary stricture, stricture resolution rate, stricture recurrence rate, stent migration, which may cause complications.…”
mentioning
confidence: 99%